Loss of carbon stock in the forests of Uttarakhand due to unprecedented seasonal forest fires - Bargali, Himanshu; Pandey, Aseesh; Bhatt, Dinesh; Sundriyal, R. C. (Frontiers in Forests and Global Change, 2024)
We extend our sincere gratitude for your invaluable review of our manuscript. Reviewers' thoughtful insights and comments have significantly enhanced the quality of our work. We are particularly thankful for your meticulous attention to detail, leading to important improvements in the methodology, discussion, and other sections. Reviewers' expertise is pivotal, and we have addressed each comment in the detailed response to reviewers' sheet below. Thank you for contributing to the refinement of our research. We look forward to the opportunity of receiving further feedback as we continue to improve our work. Please find the detailed response to the reviewers' sheet below, where we have addressed each of your comments and provided explanations for the changes made in the revised version.Reviewer 1: Reviewer (s)' comments to authorsRemark/ justification While we acknowledge that forest fire incidents can vary in intensity and impact, our selection process aimed to minimize bias by choosing a site that experienced complete burning. Singh, J., and Singh, S.P., (1992). Forests of Himalaya: Structure, functioning, and impact of man. Environmental Science, Geography.Should be provided after the text.As suggested, the figure is being provided after the text in the revised MS.